Kajian Edible Coating Berbasis Pati Singkong Dengan Perbedaan Stabilizer (Alamidan Sintetis) Pada Bakso Ayam - Maulida Fitri Iswari; Noor Harini; Sri Winarsih (Food Technology and Halal Science Journal, 2019)
The edible coating based on cassava starch is a method of giving a thin coating on food product to extend the shelf life have weakness has low barrier properties to moisture it’s required the addition of a stabilizer to extend the shelflife that applied on chicken meatball which has a short shelf life is 24 hours. The purpose of this research is to find different types and concentrations of stabilizers and determine the best treatment. The research nested. Extraction of carrageenan from seaweed(Eucheumma cotton) and extraction of pectin from green cincau leaf (Premma oblong folio) then make edible coating treated with a natural stabilizer (carrageenan and pectin) and synthetic (STPP and CMC) with 0.2%, 0.3%, and 0.4% concentration. The results showed that the type of stabilizer had significant effect on moisture content, ash content, color (L), and texture, while the concentration of stabilizer had no significant effect on moisture content, color (L), color (a+), color (b+), total plate count and scent organoleptic. The best treatment was stabilizer CMC0.3%.